THE EFFECT OF IMPORTED INTERMEDIATE-GOODS FROM CHINA TOWARDS EMPLOYMENT AND WAGE OF MANUFACTURING INDUSTRY SECTOR IN INDONESIA 2011-2018 - Ningsih Carolina Sitinjak; Evi Yulia Purwanti; Mulyo Hendarto Robertus (Riset Ekonomi Pembangunan, 2021)
This study aims to determine the effect of imports of intermediate goods from China on the employment and wages in the Indonesian Manufacturing Industry. This study uses secondary data from Badan Pusat Statistik, with cross-section data consisting of 24 sectors of the Klasifikasi Baku Lapangan Usaha Indonesia (KBLI) and time-series data for 2011-2018. The analysis tool used is the Two-Stage Least Square (TSLS) with the random effect estimation model. Endogenous variables in this research are employment and wages. Exogenous variables in the study are imports of intermediate goods from China, female workers, college workers, and added value. The results showed that employment and value-added had a positive and significant effect on wages, while the import of intermediate goods from China did not have a significant effect on wages. Meanwhile, female workers, college-workers, and wages have a positive and significant effect on employment, while imports of intermediate goods from China do not have a significant effect on employment in Klasifikasi Baku Lapangan Usaha Indonesia (KBLI) sector.